Pengaruh “Virtual Influencers” di TikTok terhadap Perilaku Konsumen Generasi Z di Kota Mataram - Jannah, Miptahul; Rizal, Ahmad Ashril (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Virtual Influencer /also called Cgi influencer are fictional characters that are created through computer technology. They are the life-like looking and personable ones who help get to audiences on social media for marketing. They can work as a virtual human that serve as a brand ambassador of the tunes & logs- the products and engage with their followers just like regular influencer. It has impacted the digital marketing status-quo on social media like no other platform (Especially TikTok). Marketing of virtual influencers to Generation Z as the largest consumer generation on social is the top priority. In general, Virtual Influencers are known to push the bar rather high when it comes to new and unique styles or trends in fashion the younger generations take to daily. Whether as “virtual Influencers” spread content that could potentially shape consumer preference around a certain apparel brand, hairstyle, accessory, etc. Problema was then later questioned as a top in article So this study intends to explore the virtual influencers' effect on TikTok of Generation Z consumption behavior in Mataram City. The analysis of data was conducted on 50 respondents using the product moment correlation test in a quantitative method through a questionnaire. The research actually highlights the impact of “Virtual Influencers” on the consumer perception in Mataram City based on Generation Z consumption behavior with a significant correlation result of r = 0.798 indicating high relationship between the two, showing that influencing factor. The effect size of 45.8% implies that 47% of the variation in how consumers merchandising decisions are driven by their interaction with virtual influencers on the TikTok platform. The researches the effect of virtual influencers on Generation Z's buying decision.